2009
DOI: 10.1096/fj.08-113944
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive peripheral immune response increases proliferation of neural precursor cells in the adult hippocampus

Abstract: To understand the link between peripheral immune activation and neuronal precursor biology, we investigated the effect of T-cell activation on adult hippocampal neurogenesis in female C57Bl/6 mice. A peripheral adaptive immune response triggered by adjuvant-induced rheumatoid arthritis (2 microg/microl methylated BSA) or staphylococcus enterotoxin B (EC(50) of 0.25 microg/ml per 20 g body weight) was associated with a transient increase in hippocampal precursor cell proliferation and neurogenesis as assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 61 publications
(80 reference statements)
3
38
1
Order By: Relevance
“…This assumption is in line with our previous results and stud-ies by others showing the influence of immuncompetent cells on hippocampal neurogenesis, particularly under systemic and local pathological conditions (Ekdahl et al, 2003;Monje et al, 2003;Wolf et al, 2009b). General autoimmune conditions are associated with altered neurogenesis in the dentate gyrus, as shown for mouse models of systemic lupus erythematodes, Type 1 diabetes, and autoimmune arthritis (Beauquis et al, 2008;Stanojcic et al, 2009;Wolf et al, 2009a). Our data suggest a complex regulation pattern: apparently autoimmune inflammation restricted to the CNS results in increased numbers of NPCs, whereas this compensatory process not necessarily leads to an enhanced net neurogenesis on the long term.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This assumption is in line with our previous results and stud-ies by others showing the influence of immuncompetent cells on hippocampal neurogenesis, particularly under systemic and local pathological conditions (Ekdahl et al, 2003;Monje et al, 2003;Wolf et al, 2009b). General autoimmune conditions are associated with altered neurogenesis in the dentate gyrus, as shown for mouse models of systemic lupus erythematodes, Type 1 diabetes, and autoimmune arthritis (Beauquis et al, 2008;Stanojcic et al, 2009;Wolf et al, 2009a). Our data suggest a complex regulation pattern: apparently autoimmune inflammation restricted to the CNS results in increased numbers of NPCs, whereas this compensatory process not necessarily leads to an enhanced net neurogenesis on the long term.…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that inflammatory processes in the brain resulting in the activation of microglia lead to decreased neurogenesis in the DG (Ekdahl et al, 2003;Monje et al, 2003). Moreover, we could previously describe a key role for CD4-positive T cells as part of the healthy adaptive immune system in supporting adult hippocampal neurogenesis (Wolf et al, 2009a) and the decrease of neuronal cell proliferation due to disturbances of the immune system homeostasis (Kipnis et al, 2001;Wolf et al, 2009b). The neurogenic effects of the interaction between the immune system and the CNS are in part mediated by the CD4-positive T cell-induced elevation of the brain-derived neurotrophic factor (BDNF).…”
Section: Introductionmentioning
confidence: 77%
“…This learning deficit was reversed 2 weeks after injection with splenocytes from wild-type mice 1214,32 . Similar results were obtained following the depletion of T cells using CD4-specific antibodies, but not when CD8-specific antibodies were used 33,34 . These results indicate that CD4 + T cells are involved (directly or indirectly) in learning behaviour.…”
Section: T Cells Make Mice Smart(er)supporting
confidence: 73%
“…Collectively, these observations suggest that autoimmune T cells play critical roles in the maintenance of fundamental function of hippocampus through the regulation of neurogenesis. In addition, other groups also reported the impacts of T cells on adult hippocampal neurogenesis (Wolf SA et al, 2009a& 2009bHuehnchen P et al, 2011), further supporting the concept that the immune system contributes to certain types of brain functions. On the contrary, in certain types of the degenerative CNS diseases, inflammatory and autoimmune responses by immune cells against the nervous system are considered to be harmful.…”
Section: The Mutual Interactions Between the Immune And The Nervous Smentioning
confidence: 59%